The use of integrated project delivery (ipd) to reduce construction claims in South African mining capital projects - Shoniwa, Kuda John (University of the Witwatersrand, Johannesburg, 2024)
The current traditional Design-Bid-Build (DBB) method on capital projects, results in adversarial relationships, insufficient collaboration, poorly defined scopes of work, inadequate designs, unsatisfactory upfront planning, and diminished integration. This often leads to various changes to planned or agreed contractor scope, schedule, cost or quality during construction resulting in numerous and expensive construction claims for additional costs and time which can be reduced by incorporating Integrated Project Delivery (IPD) benefits. In this research, reference to construction claim means a request by contractor for additional cost or extension of time during construction due to changes in planned or agreed scope, schedule, cost or quality. This research study explores the use of IPD benefits to reduce construction claims in South African mining capital projects, contracted under the traditional DBB method. The research question for this study is therefore, “How can IPD benefits be incorporated into the traditional Design-Bid-Build method so as to reduce construction claims in South African mining capital projects?”. The researcher utilised literature review, survey and focus groups, as mixed research methods. Meta-synthesis, questionnaires and interviews were employed, as data collection techniques. Qualitative analysis incorporating descriptive and pattern coding and quantitative analysis were used for data analysis. In answering the research question, a literature review meta-synthesis identified 28 major causes of construction claims including: changes in design and scope, unclear risk allocation, unclear design documents and specifications, inadequate planning and poor communication. Furthermore, 17 benefits of IPD essential to reducing construction claims were identified and included: early involvement of key participants, collaboration, joint decision making, and open communication. The findings show that there is an opportunity to use aspects of IPD and infusing them into the traditional Design-Bid-Build project delivery method to reduce construction claims. IPD benefits present an opportunity to minimize changes later in the projects which in turn assists in reducing construction claims. By understanding the root causes of construction claims and reviewing the effectiveness and deficiencies of current practices used to reduce the claims, a framework that uses identified IPD benefits as remedies to causes of construction claims in capital projects can be developed. The researcher then developed a framework incorporating IPD benefits into the traditional DBB method for South African mining capital projects, to reduce construction claims. This framework will enable project stakeholders to collaborate and integrate early to deliver quality, within budget and on-time projects so that beneficial use of the assets can commence and generate value for stakeholders. Learnings from this research will promote the required changes in behaviour and attitudes in the construction industry which can lead in the direction of full IPD implementation in the future.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Engineering and the Built Environment , School of Construction Economics and Management, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Construction Claims; Integrated Project Delivery (IPD); Mining Capital Projects; Traditional Project Delivery; Design-Bid-Build; SDG-17: Partnerships for the goals